2014
DOI: 10.1134/s0965544114060103
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic aromatization of ethane on zinc-modified zeolites of various framework types

Abstract: 420Present day development of promising novel pro cesses for the petrochemical and petroleum refining industry is largely associated with progress in zeolite catalysis. Research in the field of designing next gen eration zeolite systems having a high activity in the cracking, dehydrogenation, isomerization, and arom atization reactions opens a sound possibility of involv ing in catalytic processing of light hydrocarbons to produce valuable chemicals. Aromatization of gaseous hydrocarbons occurs in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…[7,15,18,[24][25][26][27] However, only a few studies have been dedicated to the performance and catalytic life-time enhancement of Zn-containing zeolite catalyst for ethane direct conversion to aromatics. Vosmerikova et al [28] studied the influence of zeolite framework structure for ethane dehydroaromatization on ZSM-5, ZSM-8, ZSM-11, and ZSM12 at 650°C. They demonstrated that the most effective catalyst is zinc containing ZSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…[7,15,18,[24][25][26][27] However, only a few studies have been dedicated to the performance and catalytic life-time enhancement of Zn-containing zeolite catalyst for ethane direct conversion to aromatics. Vosmerikova et al [28] studied the influence of zeolite framework structure for ethane dehydroaromatization on ZSM-5, ZSM-8, ZSM-11, and ZSM12 at 650°C. They demonstrated that the most effective catalyst is zinc containing ZSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…Although silica and alumina have been reported as strong non-reducible catalyst supports [30,31], recent studies have revealed zirconium oxides to demonstrate higher strength in working conditions [32]. It has been reported that the sulfurized form of ZrO 2 known as sulfated zirconia (SZ), actively helps the active metal sites to stabilize on the oxide support at a greater degree [29,33].…”
Section: Introductionmentioning
confidence: 99%
“…Though there is still some distance to go for ethane-to-aromatic industrialization, some important knowledge about the catalyst formulations for the ethane-to-aromatic process had been acquired by both academic groups and industrial entities since the 1970s. It is believed that ethane aromatization consists of the transformation of ethane into ethylene and the transformation of as-formed ethylene into aromatic hydrocarbons, and bifunctional catalyst components with metal sites for ethane dehydrogenation and acid sites for the oligomerization and aromatization were employed. , For metal sites, Cu, Zn, Ga, Mo, and Pt are proved to be effective for dehydrogenation of ethane. ,, Among these metals, Pt possesses powerful dehydrogenation ability but with unfortunate high hydrogenolysis side reaction that usually leads to a large amount of unwanted methane. Secondary metal (Sn, Ge, Ga, and Fe)-modified Pt had been extensively investigated to overcome the weakness of Pt metal sites.…”
Section: Introductionmentioning
confidence: 99%